A subject-specific inverse-dynamics approach for estimating joint stiffness in sideways fall. (2015) - Luo, Yunhua; Nasiri-Sarvi, Masoud
Sideways fall has been identified as the most critical situation leading to hip fracture in the elderly. The stiffness and damping property of the body joints are necessary for constructing effective biomechanical models to study fall dynamics. However, very little has been known about the joint behaviour when the body is in fall. We developed a subject specific inverse-dynamics approach to estimate the joint stiffness and damping property. The anthropometric parameters required for constructing the inverse-dynamics model was extracted from the subject's whole body dual energy X-ray absorptiometry (DXA) image. The motion data of the body in sideways fall were obtained by protected fall tests using the same subject. The joints were represented by the Kelvin-Voigt model with undetermined stiffness and damping parameters, which were then determined by solving the inverse problems. For validation purpose, the obtained joint stiffness and damping parameters were substituted back into the dynamics equations and the forward problems were solved. The predicted fall kinematic variables were compared with those measured from the fall tests. Good agreements were observed, indicating that the proposed approach is reliable and reasonably accurate.